A comparative evaluation of coal specific surface area by CO2 and N2 adsorption and its influence on CH4 adsorption capacity at different pore sizes. (1st November 2016) - Zhao, Junlong; Xu, Hao; Tang, Dazhen; Mathews, Jonathan P.; Li, Song; Tao, Shu
Highlights: Pore structures of three coal sample series were evaluated. Coal specific surface areas by CO2 and N2 adsorption were compared. Specific surface area was correlated with CH4 adsorption capacity. Theoretical support was provided for CBM refinement efficient development. Abstract: Coal has a heterogenous porosity that influences its specific surface area (SSA) and CH4 adsorption and desorption. However, the pore size distribution obtained with N2 adsorption is only reliable at pore sizes >2 nm omitting the important contribution of micropore (<2 nm). Here, 13 coal samples from three series were measured by both the N2 at 77 K and CO2 at 273 K, respectively, to compared the adsorption pore structure characteristics of different coal ranks, seams, and macrolithotypes, which further revealed the influences of mesopore (2–50 nm) and micropore on CH4 adsorption capacity at different pore sizes. The larger micropore total pore volume (TPV) contributes to the larger micropore SSA. As micropores are common and contribute extensively to most of the SSA (>99%) in these coals, a much better relationship exists between the Dubinin-Radushkevich (DR) SSA and CH4 adsorption capacity (Langmuir volume). With the increase of the coal rank, the CH4 adsorption capacity increases continuously and the DR SSA shows a tendency of first decreasing then increasing; at the same coal rank, from the bright to dull coal, the vitrinite content as well as the DR SSA and CH4 adsorption capacity decreases; for the three main coal seams in the Hancheng mine area, the No. 11 coal has the largest DR SSA and CH4 adsorption capacity followed by the No. 3 coal and No. 5 coal. With CO2 adsorption, it is more significant than N2 adsorption to accurately characterize the microscopic structure of coal and understand the gas adsorption mechanism.